A global role for KLF1 in erythropoiesis revealed by ChIP-seq in primary erythroid cells - Tallack, Michael R.; Whitington, Tom; Shan Yuen, Wai; Wainwright, Elanor N.; Keys, Janelle R.; Gardiner, Brooke B.; Nourbakhsh, Ehsan; Cloonan, Nicole; Grimmond, Sean M.; Bailey, Timothy L.; Perkins, Andrew C. (Genome Research, 2010)
KLF1 regulates a diverse suite of genes to direct erythroid cell differentiation from bipotent progenitors. To determine the local cis-regulatory contexts and transcription factor networks in which KLF1 operates, we performed KLF1 ChIP-seq in the mouse. We found at least 945 sites in the genome of E14.5 fetal liver erythroid cells which are occupied by endogenous KLF1. Many of these recovered sites reside in erythroid gene promoters such as Hbb-b1, but the majority are distant to any known gene. Our data suggests KLF1 directly regulates most aspects of terminal erythroid differentiation including production of alpha- and beta-globin protein chains, heme biosynthesis, coordination of proliferation and anti-apoptotic pathways, and construction of the red cell membrane and cytoskeleton by functioning primarily as a transcriptional activator. Additionally, we suggest new mechanisms for KLF1 cooperation with other transcription factors, in particular the erythroid transcription factor GATA1, to maintain homeostasis in the erythroid compartment.
10.1101/gr.106575.110